HARMONISASI PERATURAN DAERAH BERDASARKAN ASAS LEX SUPERIOR DEROGATE LEGI INFERIORI UNTUK MENCAPAI KEPASTIAN HUKUM DALAM SUATU PERATURAN DAERAH - Eko Hariyanto (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Harmonization of Laws and Regulations is carried out by conducting a review and discussion of the existing Regional Regulation Plans so that they do not conflict with higher laws and regulations and there is no overlap between Regional Regulations and other regional regulations. This paper will discuss the harmonization of regional regulations based on the principle of lex superior derogate legi inferiori to achieve legal certainty in a regional regulation. With normative juridical research methodology. Thoughts regarding the importance of planning for drafting laws and planning for drafting regional regulations are actually based on the need for performance improvement and evaluation of legislation, as well as a systematic and well-programmed inventory of laws and regulations, so as to make the process of formulating laws and regional regulations run as expected, both from the beginning of the planning process until there is joint agreement in plenary between the DPR/DPRD and the President/Regional Government, as well as the planning of other laws and regulations which must comply with the principle of lex superior derogate legi inferiori to achieve legal certainty in a regional regulation. Apart from planning laws, planning regional regulations also has an important and strategic position in our legal system. Because Regional Regulations are recognized in the legal system in Indonesia and since amendments were made to the 1945 Constitution, specifically Article 18 paragraph (6) of the 1945 Constitution and based on Law Number 13 of 2022 the Second Amendment to Law Number 12 of 2011 concerning the Formation of Laws and Regulations, the position of Regional Regulations in the Indonesian legal system is becoming stronger as one type of legislation that applies and is generally binding.Keywords: Harmonization, Regional Regulation, lex superior derogate legi inferiori.